Atherogenesis, Transcytosis, and the Transmural Cholesterol Flux: A Critical Review. (14th April 2022) - Goldberg, Doron; Khatib, Soliman
Abstract : The recently described phenomenon of cholesterol-loaded low-density lipoproteins (LDL) entering the arterial wall from the lumen by transcytosis has been accepted as an alternative for the long-held concept that atherogenesis involves only passive LDL movement across an injured or dysfunctional endothelial barrier. This active transport of LDL can now adequately explain why plaques (atheromas) appear under an intact, uninjured endothelium. However, the LDL transcytosis hypothesis is still questionable, mainly because the process serves no clear physiological purpose. Moreover, central components of the putative LDL transcytosis apparatus are shared by the counter process of cholesterol efflux and reverse cholesterol transport (RCT) and therefore can essentially create an energy-wasting futile cycle and paradoxically be pro- and antiatherogenic simultaneously. Hence, by critically reviewing the literature, we wish to put forward an alternative interpretation that, in our opinion, better fits the experimental evidence. We assert that most of the accumulating cholesterol (mainly as LDL) reaches the intima not from the lumen by transcytosis, but from the artery's inner layers: the adventitia and media. We have named this directional cholesterol transport transmural cholesterol flux (TCF). We suggest that excess cholesterol, diffusing from the avascular (i.e., devoid of blood and lymph vessels) media's smooth muscle cells, is cleared by the endothelium through its apical membrane. A plaque is formed when this cholesterol clearance rate lags behind its rate of arrival by TCF.